The War in the Self: The Influence of Impostor Syndrome and Academic Resilience on Academic Anxiety - Putri, Nanda Revalinha; Ramadhani, Ayunda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to determine the influence of Impostor Syndrome tendency and academic resilience on academic anxiety. The research method used is quantitative. The subjects of this study are 55 undergraduate students of the Faculty of Economics and Business, Mulawarman University, Samarinda who are pursuing strata 1 with purposive sampling data collection techniques. The data analysis technique used is multiple linear regression. The collected data was analyzed with the help of the Statistical Package for Social Science (SPSS) version 26.0 for windows program. The results showed that (1) there was a significant influence of Impostor Syndrome and academic resilience on academic anxiety with a value of F Count = 16.133 F Table = 3.18 and p = 0.000 0.05 and an influence contribution of 38.3%; (2) there was no significant effect of Impostor Syndrome on academic anxiety with a value of beta coefficient (β) = 0.162, t count = 1.152, and p = 0.225 (p 0.05); (3) There was a significant effect of academic resilience on academic anxiety with a value of beta coefficient (β) = -0.503, t count = 3.564, and p = 0.002 (p 0.05).